Google SketchUp 7 for dummies - Chopra, Aidan (--For dummies., 2009)
In classic "For Dummies" tradition, "Google SketchUp 7 For Dummies" gets right to the point so you can start creating 3D models right away; use the LayOut function to draw with vector tools; export your models to other design programs or to Google Earth; and explore 3D animation. On the book's companion Web site, you'll also find a bonus chapter and videos demonstrating more about what you can do with Google SketchUp. "Google SketchUp 7 For Dummies" also shows you what SketchUp can and can't do, and offers tips for solving common problems.